Penerapan Model Pembelajaran Problem Based Learning dalam Materi Dinamika Atmosfer untuk Meningkatkan Hasil Kemampuan Berpikir Analitis Siswa Kelas X-5 Di SMA Negeri 1 Sidoarjo: APPLICATION OF THE PROBLEM BASED LEARNING MODEL IN ATMOSPHERIC DYNAMICS TO IMPROVE THE RESULTS OF THE ANALYTICAL THINKING ABILITY OF CLASS X-5 STUDENTS AT SMA NEGERI 1 SIDOARJO - Nisa, Istikharotul Khoirun; Kurniawati, Aida (J-SES : Journal of Science, Education and Studies, 2024)
In learning geography requires students to be able to improve their high-level thinking skills, namely the ability to think analytically. Analytical thinking makes students able to overcome and also be able to deal with all the problems that are being faced easily, so that by using the ability to think analytically students can solve the problems they face. The steps that can be taken by the teacher to improve analytical skills are by using the Problem-based Learning (PbL) learning model. This research was conducted in class X-5 which aims to find out how the application of the PbL model is used to improve the results of analytical thinking skills in the geography learning process in class X-5 SMAN 1 Sidoarjo. This research uses class action research model Suharsimi Arikunto by using quantitative descriptive data analysis techniques with primary data sources and secondary data. Data collection techniques used were pretest-posttest, observation, and documentation. The results of the study show that the application of the problem-based learning model can improve the results of students' analytical thinking skills in learning geography on atmospheric dynamics material in class X-5 SMAN 1 Sidoarjo in the 2022/2023 academic year. The increase can be seen from the overall average test results for students' analytical thinking skills from initially 51.35% to 68.92% in cycle I and increased again to 88.65% in cycle II.